Eight coordinated mononuclear dysprosium complexes of heptadentate aminophenol ligands: the influence of the phenol substituents and the ancillary donors on the magnetic relaxation. Issue 43 (28th October 2021) - Fondo, Matilde; Corredoira-Vázquez, Julio; García-Deibe, Ana M.; Sanmartín-Matalobos, Jesús; Reta, Daniel; Colacio, Enrique
Abstract : Distorted square antiprism Dy III SIMs of heptadentate aminophenol ligands decrease their U eff with the electron-withdrawing ability of the phenol substituents and the increasing electronegativity of auxiliary monodentate donors. Abstract : The mononuclear complexes [Dy(3Br, 5Cl-H3 L 1, 1, 4 )(D)]·solvate (D = H2 O, solvate = 0.25MeOH, 1W ·0.25MeOH; D = Py without solvate, 1Py ), and [Dy(3NO2, 5Br-H3 L 1, 1, 4 )(H2 O)] (2W ) were isolated. The crystal structures of 1W ·0.25MeOH, 1Py and 2W ·2CH3 C6 H5 show that the Dy III ion is octacoordinated, in N 4 O 4 or N 5 O 3 environments, with distorted geometries, between square antiprism, biaugmented trigonal prism and triangular dodecahedral. A similar environment for the metal ion is shown in the chiral crystals of the diamagnetic yttrium analogue [Y(3Br, 5Cl-H3 L 1, 1, 4 )(MeOH)] (3M ), which were spontaneously resolved. Magnetic analyses of the three dysprosium complexes, and their diluted analogous 1W @Y, 1Py @Y and 2W @Y, reveal that none of them seem to relax through an Orbach mechanism at H dc = 0. However, the three complexes show Orbach relaxation under H dc = 1000 Oe, and 1Py is the in-field SIM with the highest energy barrier among these complexes, with a U eff value of 358 K. Analysis of ac magnetic data shows that the electron-withdrawing substituents on the phenol rings of the aminophenol ligands, as well as the auxiliary oxygen donors from water ligands, reduce the energy barriers of the complexes, which is attributed to a charge reduction in the coordinating atoms of the aminophenol donor. Ab initio calculations support the experimental results.